Bilingual acquisition during school years: predictors of achievement in the societal and heritage language - Grose-Hodge, Magdalena; Dabrowska, Ewa; Divjak, Dagmar (Frontiers in Language Sciences, 2025)
There are vast individual differences in heritage bilinguals' linguistic skills. It is not clear, however, to what extent this variation can be attributed to experience, cognitive ability or motivation. This study investigates factors influencing the acquisition of both Polish (HL = Heritage Language) and English (SocL = Societal Language) of school-age children, examining the role of motivation, linguistic experience, and language aptitude. We collected and analyzed speech samples from 7- to 12-year-old participants (n = 78) residing in the UK to derive linguistic measures of fluency, syntactic complexity and lexical diversity in both languages. Additionally, a receptive grammar test was administered. Independent variables were obtained via parental questionnaires, a motivation survey and a language aptitude test. To identify predictors of heritage bilingual acquisition, we conducted least squares linear regression analyses for each language area and applied backward stepwise selection to reduce the models. Results show that predictors differ between languages and linguistic areas. Our findings highlight the role of language aptitude in bilingual development, challenge assumptions that motivation to use HL might detract from SocL development, and suggest that HL acquisition can support, rather than hinder, societal language development, as bilingual children draw on their metalinguistic awareness and cognitive skills across both languages.